Rhizobium Inoculation and Phosphorus Application on Nodulation and Yield of Common Bean in Ethiopia - Hulluager Abebe; Birhan Getie; Tiringo Yilak; Tiruneh Gizachew Ayalew (Legume Science, 2025)
ABSTRACT In Ethiopia, the cultivation of common beans is hindered by the lack of nitrogen and phosphorus nutrients in the soil. To address this issue and enhance the production of common beans, a sustainable approach involving the use of nitrogen‐fixing microbial inoculants and an adequate supply of phosphorus nutrients was investigated. A field experiment was conducted at Tach Gayint during the main cropping seasons of 2021 and 2022 with site one and site two. A randomized complete block design was used comprising 12 treatments, which included combinations of Rhizobium strains (uninoculated, Native/A15, and Native/429) and phosphorus rates (0, 50, 100, and 150 kg P2O5 ha−1). Data of plant height, number of pods per plant, days to physiological maturity, days to 50% flowering, total number of nodules per plant, quantity of seeds in each pod, the weight of 100 seeds in grams, and the grain production in kilograms per hectare were collected. The Statistical Analysis System Software, Version 9.0 was utilized for this analysis. The results of the interaction effect revealed that significant difference among treatments. The treatment with 50 kg P2O5 ha−1 exhibited the maximum number of seeds per pod (5.5), pods per plant (13.3), and hundred seed weight (22.5). The highest grain yield (2378 kg ha−1) was obtained when the Native/429 strain was inoculated with 50 kg P2O5 ha−1. Based on the findings of this study, it was recommended to inoculate the local isolate 429 with a phosphorus application rate of 50 kg P2O5 ha−1.